Chromosome number diversity in Asian Cryptocercus (Blattodea, Cryptocercidae) and implications for karyotype evolution and geographic distribution on the Western Sichuan Plateau. Issue 6 (18th August 2019) - Wang, Lili; Liao, Shuran; Liu, Minglun; Deng, Wenbo; He, Jiajun; Wang, Zongqing; Che, Yanli
Abstract : Cryptocercus cockroaches are remarkable for their similarity in external morphology while having a diversity in chromosome numbers. Most species are therefore delimited by karyotyping combined with phylogenetics. However, the investigation of chromosome diversity within a limited region is not well-studied, and the causes of their geographic distribution patterns remain unclear. Here, we applied a multipronged set of analyses that included external morphological analysis, chromosomal data, molecular species-delimitation methods and phylogenetic reconstruction after extensive sampling on the Western Sichuan Plateau (WSP) in western China. As a result, six new species were discovered, which increases the known species in WSP to 15. Multiple extinction-isolation events caused by the lifting of the Qinghai-Tibetan Plateau and by glacial periods likely account for the present-day distribution of WSP species. For Manchurian species, major extinctions may have been caused by the Quaternary glaciation and Cenozoic volcanic activities. We believe that three factors shaped the current distribution of Cryptocercus karyotypes: (1) a variability of chromosomes, (2) their low capability for dispersal, and (3) their vulnerability to climate change. http://www.zoobank.org/:urn:lsid:zoobank.org:pub:03E4D351-4C0C-48F9-9BBD-7063FDC2DED7